Identifying and Classifying User Typologies Within a United Kingdom Hospital Library Setting: A Case Study - Easton, Lynn; Adam, Scott; Durnan, Trish; McLeod, Lorraine (Evidence Based Library and Information Practice, 2016)
Objective – To identify available health library user typology classifications and, if none were suitable, to create our own classification system. This is to inform effective future library user engagement and service development due to changes in working styles, information sources and technology. Methods – No relevant existing user typology classification systems were identified; therefore, we were required to create our own typology classification system. The team used mixed methods research, which included literature analysis, mass observation, visualization tools, and anthropological research. In this case study, we mapped data across eleven library sites within NHS Greater Glasgow and Clyde Library Network, a United Kingdom (U.K.) hospital library service. Results – The findings from each of the NHS Greater Glasgow and Clyde Library Network’s eleven library sites resulted in six user typology categories: e-Ninjas, Social Scholars, Peace Seekers, Classic Clickers, Page Turners and Knowledge Tappers. Each physical library site has different profiles for each user typology. The predominant typology across the whole service is the e-Ninjas (28%) with typology characteristics of being technically shrewd, IT literate and agile – using the library space as a touch down base for learning and working. Conclusions – We identified six distinct user types who utilize hospital library services with distinct attributes based on different combinations of library activity and medium of information exchange. The typologies are used to identify the proportional share and specific requirements, within the library, of each user type to provide tailored services and resources to meet their different needs.